Answer:
5)x=0,y=-4
6)x=8&y=6
Explanation:
5)x+7y=-28
3x-5y=20
x=0, y=-4
for x+7y=-28 let's get "x" by itself, so bring 7y to the right
x=-28-7y
now that we have the value of "x"let's substitute it in "3x-5y=20"
3(−7y−28)−5y=20
-21y-84-5y=20
−26y−84=20(Simplify both sides of the equation)
−26y−84+84=20+84(Add 84 to both sides)
−26y=104
−26y /-26=104/-26
(Divide both sides by -26)
y=−4
Step: Substitute−4 for y in "x=−7y−28:"
x=−7y−28
x=(−7)(−4)−28
x=0(Simplify both sides of the equation)
Answer:
x=0 and y=−4
USE THIS METHOD FOR #6 as well hope this helps!